Knowledge, attitudes, and support needs of obstetric and gynecological nurses and midwives toward perinatal mental health disorders screening in Central China: a multicenter cross-sectional survey - Zhu, Luyang; Pan, Xinlong; Chen, Chunli; Chen, Jianfei; Pan, Yuanrui; Chen, Xiaoli; Zou, Zhijie; Li, Chengqiu (Frontiers in Public Health, 2024)
Background The perinatal period is a time of increased vulnerability regarding maternal mental health status. Although guidelines and policies have been published for perinatal mental health disorders (PMHDs) screening in China, the knowledge, attitudes, and support needs of nurses and midwives toward implementing mental health screening programs during pregnancy remain unclear. Thus, this study aimed to investigate the knowledge of PMHDs, attitudes and support needs related to implementing mental health screening during pregnancy among obstetrics and gynecology (OB/GYN) nurses and midwives in the central region of China while identifying the related influencing factors. Methods A cross-sectional survey was conducted in 14 cities in Hubei, China, using convenience sampling from July to October 2023. The Chinese version of the Perinatal Mental Health Knowledge Questionnaire, the Chinese version of the Perinatal Mental Health Attitudes Scale, and the Health Care Facilities Support Needs Scale were used to investigate the PMHDs knowledge, attitudes, and support needs of OB/GYN nurses and midwives, respectively. Data were analyzed using SPSS version 27.0. Descriptive and inferential statistics were performed, with a p-value of <0.05 considered statistically significant. Results The average scores for knowledge, attitudes, and support needs were 6.09 ± 1.99 (total score: 13), 47.67 ± 8.80 (total score: 80), and 29.35 ± 4.66 (total score: 35), respectively. After adjusting for years of nursing experience and years of obstetrics and gynecology nursing experience, the multivariate logistic regression analysis indicated that having mental health-related education or work experience [adjusted OR (aOR) = 1.43, p = 0.01], being midwives (aOR = 1.78, p < 0.001), and working in specialist maternity hospitals (aOR = 1.55, p < 0.001) were significantly associated with higher knowledge scores; having mental health related education or work experience (aOR = 1.59, p = 0.014) and working in specialist maternity hospitals (aOR = 1.42, p < 0.01) were significantly associated with higher support needs scores. Conclusion OB/GYN nurses and midwives demonstrated insufficient knowledge and moderate attitudes toward PMHDs screening, and have great support need for PMHDs screening. To address these issues, medical organizations and relevant government sectors should enhance training for nurses and midwives on PMHDs and provide professional support to promote routine maternal mental health screening programs and improve perinatal mental health outcomes.